A Naturally Occurring Single Nucleotide Polymorphism in the Salmonella SPI-2 Type III Effector srfH/sseI Controls Early Extraintestinal Dissemination - Thornbrough, Joshua M. (Public Library of Science, 2012)
CD18 expressing phagocytes associated with the gastro-intestinal (GI) epithelium can shuttle Salmonella directly into the bloodstream within a few minutes following microbial ingestion. We have previously demonstrated that Salmonella controls the CD18 pathway to deeper tissue, manipulating the migratory properties of infected cells as an unappreciated component of its pathogenesis. We have observed that one type III effector, SrfH (also called SseI) that Salmonella secretes into infected phagocytes manipulates the host protein TRIP6 to stimulate their migration. Paradoxically, SrfH was shown in another study to subvert a different host protein, IQGAP1, in a manner that inhibits the productive motility of such cells, perhaps to avoid interactions with T cells. Here, we resolve the discrepancy. We report that one naturally occurring allele of srfH promotes the migration of infected phagocytes into the bloodstream, while another naturally occurring allele that differs by only a single nucleotide polymorphism (SNP) does not. This SNP determines if the protein contains an aspartic acid or a glycine residue at position 103 and may determine if SrfH binds TRIP6. SrfH Gly103 is a rare allele, but is present in the highly invasive strain Salmonella enterica serovar Typhimurium UK-1 (stands for universal killer). It is also present in the genome of the only sequenced strain belonging to the emerging pandemic Salmonella enterica serovar 4, [5],12,i:-, which is frequently associated with septicemia. Finally, we present evidence that suggests that Gifsy-2, the bacteriophage upon which srfH resides, is present in a clinical isolate of the human-specific pathogen, Salmonella enterica serovar Typhi. These observations may have interesting implications for our understanding of Salmonella pathogenesis.